Technology and governance : making technology work for society - Jaspers, Casper, ....- (Amsterdam : Prometheus, 2021)
The relationship between humans and technology is one of immense progress. It encompasses many life-changing inventions such as fire and electricity, which have had a positive impact on humanity overall. But technology is developing so rapidly that we rarely take a moment to reflect on whether we are shaping technology or whether it is shaping us. How much do you know about key technologies such as artificial intelligence, blockchain and the internet of things? And do you understand how technology affects us and why ethics plays such an essential role in both its design and its real-world application? Technology and Governance allows you to get up to speed with fast-paced technological changes. The author takes complex technical ideas and distils them into user-friendly concepts. Even if you lack detailed knowledge of the mathematics behind deep learning or the computer code behind digital currencies, this book will provide an understanding of disruptive technology's present and future impact on society.
Keywords: Maatschappij ; technologie